2020
DOI: 10.3390/molecules25214902
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Computational Studies as Analytical and High-Resolution Structural Tool for Complex Hydroperoxides and Diastereomeric Endo-Hydroperoxides of Fatty Acids in Solution-Exemplified by Methyl Linolenate

Abstract: A combination of selective 1D Total Correlation Spectroscopy (TOCSY) and 1H-13C Heteronuclear Multiple Bond Correlation (HMBC) NMR techniques has been employed for the identification of methyl linolenate primary oxidation products without the need for laborious isolation of the individual compounds. Complex hydroperoxides and diastereomeric endo-hydroperoxides were identified and quantified. Strongly deshielded C–O–O–H 1H-NMR resonances of diastereomeric endo-hydroperoxides in the region of 8.8 to 9.6 ppm were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…Additionally, while the literature suggested that very large basis sets are needed to obtain accurate NMR predictions ( Taubert et al, 2005 ), we did not find this to be the case for our system as our top-performing NMR FBS combinations did not have particularly large basis sets. These findings, in agreement with similar observations by Kupka et al (2010) and Ahmed et al (2020) , highlighted the fact that generalized rules of using large basis sets do not inherently lead to accurate chemical shift predictions and thereby necessitate the evaluation of the efficacy of each combination.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, while the literature suggested that very large basis sets are needed to obtain accurate NMR predictions ( Taubert et al, 2005 ), we did not find this to be the case for our system as our top-performing NMR FBS combinations did not have particularly large basis sets. These findings, in agreement with similar observations by Kupka et al (2010) and Ahmed et al (2020) , highlighted the fact that generalized rules of using large basis sets do not inherently lead to accurate chemical shift predictions and thereby necessitate the evaluation of the efficacy of each combination.…”
Section: Discussionsupporting
confidence: 89%
“…As a result, these methods are often unable to distinguish between diastereomers or account for interspatial coupling ( Willoughby et al, 2014 ; Benassi, 2017 ), greatly hindering the elucidation of stereochemistry within a polysaccharide. On the other hand, quantum mechanical (QM) approaches to predicting NMR shifts have been more successful in aiding experimentalists to improve the reliability of NMR and correlate the spectra to the structure by predicting the chemical shift values of complex compounds ( Pierens, 2014 ; Tarazona et al, 2018 ; Ahmed et al, 2020 ). This approach has even been used to correct previously misassigned spectra that relied on experimental databases and empirical-based predictions ( Pierens, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of methyl linolenate in atmospheric oxygen in a glass vial for 48 h at 40 °C resulted in a significant number of sharp (Δν 1/2 ≤ 2.0 Hz) of the hydroperoxide protons in the region of 7.7 to 9.6 ppm [ 138 ] ( Figure 42 ). Addition of 1 to 2 microdrops of D 2 O resulted in the elimination of several of these signals, including those in the strongly deshielded region of the aldehyde protons ( Figure 43 ).…”
Section: Nmr Spectroscopy In Mixture Analysismentioning
confidence: 99%
“…it was also attributed to an oxidation product. The broad signals at δ 7.88 and 7.79 belong to OO H protons of hydroperoxides such as 16-OOH and 9-OOH; however, these chemical shifts are sensitive to hydrogen bonds and other sample conditions [ 21 ]; thus, comparisons with other samples and literature should be done with caution. TOCSY also shows the connections between the glyceridic protons of 1,2-DG, which share a common coupling pathway.…”
Section: Resultsmentioning
confidence: 99%